Effect of ionised (electrolysed) water on the rat embryo development - Stankevič, Jolita; Audickaitė, Aistė; Šilovė, Simona; Šimčikas, Valdas; Cesiulis, Henrikas; Skujienė, Grita; Bukelskienė, Virginija; Žalgevičienė, Violeta; Tutkuvienė, Janina (Journal of Environmental Engineering and Landscape Management, 2020)
The aim of this study was to investigate the effects ionised water has on embryonic development using Wistar rat animal model. For that purpose, alkaline and acidic water was prepared with a domestic water ioniser. It was found that the concentrations of Cl–, SO42– ions increased in acidic water, while in alkaline water, Ca2+ concentration decreased and halogenated hydrocarbon concentrations exceeded permitted levels. The animals were given test alkaline and acidic water, as well as tap water as control. After three months, female rats were mated. On the 21st day of gestation, they were euthanized and subjected to Caesarean sections; the number of live and dead fetuses was recorded. The fetuses were examined for external or visceral malformations and skeletal abnormalities. The data showed that embryo death was higher in acidic and alkaline experimental groups in comparison to the control group. The fetuses in both test groups were significantly shorter than in the control group. Long bones of fetal hind and front limbs were shorter in the acidic group in comparison to the control group. Retardation of limb osteogenesis was expressed in the acidic group fetuses. Therefore, in our model, ionised water had a negative effect on the embryonic development.